(untitled) (Bangladesh Journal of Dental Research & Education, 2014)
Objectives: To find out the proportion, to determine the average length of stay at hospital and to estimate the cost of treatment for hospital-acquired infections in a tertiary level hospital of Rangpur City. Materials and Methods: This descriptive type of cross sectional study was conducted on purposively selected 200 admitted patients in a tertiary level hospital. Among them 100 were HAI patients and 100 were non HAL Data were collected through duly pretested interviewer administered questionnaire and observation checklist. Place and period of study: This study was conducted in Rangpur Medical College Hospital (RpMCH), Rangpur from January to June2011. Results: In this cross sectional study the highest percentage of HAI (42%) belonged to the surgery ward and the lowest percentage (19.%) belonged to medicine ward of the study hospital. According to the type of infections the surgical wound infection was found on the top (23%) and the cannula-associated infection at the bottom (5%) of the list. Respondents of both the polar age groups (<21 years and > 60 years) were found to be equally (27%) affected by HAI. Occurrence of HAI was found higher (57%) among the female respondents than their male (43%) counterparts. Highest number (48%) of HAI and lowest number (14%) of non- HAI patients were found to be visited by maximum number (?5) of visitors. Among the respondents who developed HAI, 42% had to stay at hospital for longest duration (21-25 days) but only 13% of their non- HAI counterparts had to stay for same duration. Among HAI patients 26% had to spend highest amount of money (Tk.20,0011- 25,0001-) but among non- HAI patients only 10% had to spend same amount of money for their treatment purpose. Conclusion: It has been revealed from this study that the occurrence of HAI was found higher among the patients with maximum number of visitors. Average length of hospital stay and cost of treatment of HAI patients were found higher than those of their non-HAI counterparts. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20247 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 49-52